Ethnobotanical Knowledge of Plant Ingredients Among Sellers of Jamu Ngadirgo Semarang - Husain, Fadly; Sary, Dian Puspita; Fajar, Fajar; Iswari, Rini; Wahidah, Baiq Farhatul (Universitas Negeri Semarang, 2020)
Traditional medicine is a medical resource that can be accessed easily by communities. Utilization of plants as herbal concoction such as jamu is one of the medical resource. There are some variations of plants species utilized in herbal medicine of jamu. Therefore, it is necessary to do a lot of studies on knowledge of jamu types and the variety of plants used in it. The research was conducted in Ngadirgo, Semarang City, where many residents work as jamu seller. By using qualitative research method and applying interview and observation technique, this research examines the ethnobotanical knowledge of jamu as herbal medicine and identifies various of plant species used in the concoction. The findings of this research show that the ethnobotanical knowledge of jamu sellers is generally obtained from older family. There are 17 types of jamu usually produced which can be distinguished as daily jamu and special jamu made by adjusting to customer order. In producing various types of jamu, the sellers use about 50 plants species as ingredients in jamu concoction. They obtain the plants by buying from the local market, and taking from their house yard or garden. This research can contribute in the conservation of community knowledge on herbal jamu and the plants used in it, as a unique identity of Javanese traditional medicine.